Step 1) Solve the first equation for #x#:

#x + 2y = 1#

#x + 2y - color(red)(2y) = 1 - color(red)(2y)#

#x + 0 = 1 - 2y#

#x = 1 - 2y#

Step 2) Subsitute #1 - 2y# for #x# in the second equation and solve for #y#:

#-3x - 8y = -9# becomes:

#-3(1 - 2y) - 8y = -9#

#(-3 * 1) - (-3 * 2y) - 8y = -9#

#-3 - (-6y) - 8y = -9#

#-3 + 6y - 8y = -9#

#-3 + (6 - 8)y = -9#

#-3 - 2y = -9#

#color(red)(3) - 3 - 2y = color(red)(3) - 9#

#0 - 2y = -6#

#-2y = -6#

#(-2y)/color(red)(-2) = -6/color(red)(-2)#

#(color(red)(cancel(color(black)(-2)))y)/cancel(color(red)(-2)) = 3#

#y = 3#

Step 3) Substitute #3# for #y# in the solution to the first equation at the end of Step 1 and calculate #x#:

#x = 1 - 2y# becomes:

#x = 1 - (2 * 3)#

#x = 1 - 6#

#x = -5#

The solution is: #x = -5# and #y = 3# or #(-5, 3)#